Einkommen und Kreditschulden privater Haushalte; Income and credit debt of private households - Markus M. Grabka; Berenike Bartz (Wirtschaftsdienst, 2022)
– This article describes the development of the needs-weighted net household income of persons in private households in Germany since the year 2000. It also focuses on the presentation of the prevalence and amount of credit debts of private households. The central result is that the share of repayments for loans in Germany has been declining overall since 2000. In particular, the share of households that spend more than 30 % of their household net income on loan repayments has halved over the last 20 years. Despite this overall positive development, there is a risk that the problem of over-indebtedness in Germany could increase again since on the one hand, many self-employed people have suffered high turnover losses due to the containment measures of the coronavirus pandemic, while on the other, the ECB could raise nominal interest rates due to tightened inflation, which would lead to a considerable financial burden for indebted households.
Keywords: G51; I39; D31; 330; Einkommen; Kredit; Private Verschuldung; Deutschland